Resin composition for sealing material, sealing material using the same, and solid polymer fuel cell and water electrolysis apparatus using the sealing material
The resin composition with acrylic and epoxy components addresses the lack of reworkability and adhesion in fuel cell sealing materials by optimizing the acrylic resin's glass transition temperature and layer bonding, enhancing reworkability and adhesion in fuel cell and water electrolyzer applications.
Patent Information
- Application Number
- JP2023096213
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-12
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-06-12
AI Technical Summary
Existing fuel cell sealing materials lack reworkability and sufficient adhesion between sealant layers, particularly in configurations where layers face and adhere to each other, which is not addressed by prior art.
A resin composition comprising an acrylic resin with specific glass transition temperature, combined with an epoxy resin and curing agent, optimized to improve reworkability and adhesion, using a copolymer of methyl methacrylate, styrene, and glycidyl (meth)acrylate, with controlled ratios and molecular weights to enhance layer bonding.
The resin composition achieves improved reworkability and enhanced adhesion between sealing material layers, maintaining adhesion under high temperature and humidity conditions, and preventing layer foaming.
Smart Images

Figure 2024177848000003 
Figure 2024177848000004 
Figure 2024177848000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition for a sealing material for a polymer electrolyte fuel cell, a sealing material using the resin composition, and a polymer electrolyte fuel cell and a water electrolysis device using the sealing material. [Background technology]
[0002] A polymer electrolyte fuel cell (hereinafter sometimes referred to as a "fuel cell") generates electricity and heat simultaneously by electrochemically reacting a fuel gas containing hydrogen with an oxidant gas containing oxygen. 1 shows a cross-sectional view of a cell 10, which is a constituent unit of a typical fuel cell. A typical fuel cell is constructed by stacking several tens to several hundreds of cells 10. The cell 10 has a seal material 16 for the purpose of fixing the electrolyte membrane 11, etc.
[0003] As fuel cell sealing materials, for example, the techniques of Patent Documents 1 and 2 have been proposed. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2016-94581 A [Patent Document 2] JP 2015-2029 A Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, in order to reduce the burden on the environment, there is a demand for increasing the yield of each product. For this reason, fuel cell sealants are required to have the ability to correct their position after application. In this specification, the above-mentioned ability may be referred to as "reworkability." Patent Documents 1 and 2 do not consider reworkability at all.
[0006] It is believed that the reworkability of fuel cell sealants can be improved by reducing the tack of the sealant layer. However, in recent years, cells have been used that have regions where the sealant layers face each other and are bonded together, as shown in Figure 2. In such cells, when the tack of the sealant layer is reduced, there is a problem that the adhesion between the sealant layers becomes insufficient.
[0007] An object of the present invention is to provide a resin composition for a sealing material, which can improve reworkability and adhesion between sealing material layers, a sealing material using the resin composition, and a solid polymer electrolyte fuel cell and a water electrolysis device using the sealing material.
[0008] In order to solve the above problems, the present invention provides the following [1] to
[11] . [1] A resin composition for a sealing material, comprising: The resin composition contains (A) an acrylic resin, (B) an epoxy resin, and (C) an epoxy resin curing agent, The (A) acrylic resin has a glass transition temperature of 5° C. or more and 35° C. or less, The (A) acrylic resin is a copolymer of raw material monomers including (a1) methyl methacrylate, (a2) styrene, and (a3) glycidyl (meth)acrylate, The proportion of the (a3) glycidyl (meth)acrylate relative to the total amount of the raw material monomers is less than 3.0 mass%, A resin composition, wherein a total content of the (B) epoxy resin and the (C) epoxy resin curing agent is 1 part by mass or more and 30 parts by mass or less per 100 parts by mass of the (A) acrylic resin. [2] The resin composition according to [1], wherein the (B) epoxy resin is at least one selected from the group consisting of phenol novolac type epoxy resins, bisphenol A type epoxy resins, and bisphenol F type epoxy resins. [3] The resin composition according to [1] or [2], wherein the epoxy equivalent of the (B) epoxy resin is 150 g / eq or more and 1500 g / eq or less. [4] The resin composition according to any one of [1] to [3], wherein the (C) epoxy resin curing agent is a polyamine-based curing agent. [5] A sealing material formed from the resin composition described in [1]. [6] A sealant having a first substrate, a sealant layer, and a second substrate in this order, the sealant layer being formed from the resin composition according to any one of [1] to [4], and at least one of the first substrate and the second substrate being peelable. [7] The sealing material according to [5] or [6], which is a sealing material for a polymer electrolyte fuel cell. [8] The sealing material according to [5] or [6], which is a sealing material for a water electrolysis device. [9] A polymer electrolyte fuel cell having a sealing portion formed by the sealing material described in [7].
[10] The solid polymer electrolyte fuel cell according to [9], wherein the solid polymer electrolyte fuel cell has an area in which the sealing material layers face each other and are bonded to each other.
[11] A water electrolysis device having a sealing portion made of the sealing material described in [8]. Effect of the Invention
[0009] The resin composition for a sealing material of the present invention, a sealing material using the resin composition, and a solid polymer electrolyte fuel cell and a water electrolysis device using the sealing material can have good reworkability and good adhesion between sealing material layers. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a cross-sectional view showing an example of a cell constituting a fuel cell. [Diagram 2] FIG. 4 is a cross-sectional view showing a portion of another example of a cell that constitutes a fuel cell. [Diagram 3] FIG. 2 is a cross-sectional view showing an example of a sealing material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] [Resin composition for sealing material] The resin composition for a sealing material of the present invention comprises: (A) an acrylic resin, (B) an epoxy resin, and (C) an epoxy resin curing agent; The (A) acrylic resin has a glass transition temperature of 5° C. or more and 35° C. or less, The (A) acrylic resin is a copolymer of raw material monomers including (a1) methyl methacrylate, (a2) styrene, and (a3) glycidyl (meth)acrylate, The ratio of the (a3) glycidyl (meth)acrylate to the total amount of the raw material monomers is less than 3.0 mol %, The total content of the (B) epoxy resin and the (C) epoxy resin curing agent is 1 part by mass or more and 30 parts by mass or less per 100 parts by mass of the (A) acrylic resin.
[0012] <(A) Acrylic resin> (A) The acrylic resin is a copolymer of raw material monomers including (a1) methyl methacrylate, (a2) styrene, and (a3) glycidyl (meth)acrylate.
[0013] The (A) acrylic resin is a main component of the resin composition. The content of the (A) acrylic resin relative to the total amount of the resin composition is preferably 77% by mass or more and 99% by mass or less, more preferably 80% by mass or more and 99% by mass or less, and even more preferably 85% by mass or more and 99% by mass or less.
[0014] The (A) acrylic resin must have a glass transition temperature of 5° C. or higher and 35° C. or lower. If the glass transition temperature is lower than 5° C., the reworkability cannot be improved. If the glass transition temperature is higher than 35° C., the adhesion between the sealing material layers cannot be improved. The glass transition temperature of the (A) acrylic resin is preferably 5°C or higher and 27°C or lower, and more preferably 5°C or higher and 20°C or lower.
[0015] The glass transition temperature of the (A) acrylic resin can be adjusted, for example, by the weight average molecular weight of the (A) acrylic resin. Increasing the weight average molecular weight increases the glass transition temperature, whereas decreasing the weight average molecular weight tends to decrease the glass transition temperature. The glass transition temperature of the acrylic resin (A) can also be adjusted by the use of ethyl (meth)acrylate (a4) described below. Increasing the ratio of ethyl (meth)acrylate (a4) to the total amount of raw material monomers tends to lower the glass transition temperature, whereas decreasing the ratio of ethyl (meth)acrylate (a4) to the total amount of raw material monomers tends to raise the glass transition temperature. In this specification, the weight average molecular weight is a value measured by gel permeation chromatography (GPC) and converted into polystyrene equivalent.
[0016] (a1) Methyl methacrylate By including (a1) methyl methacrylate as a raw material monomer of (A) acrylic resin, for example, the following effects i) to iii) can be expected. On the other hand, if the content ratio of (a1) methyl methacrylate is too high, the hardness of the sealant layer increases, and it may become difficult to follow the shape of the adherend. For this reason, it is preferable to adjust the content ratio of (a1) methyl methacrylate in consideration of the balance between the following effects i) to iii) and the hardness of the sealant layer. i) The glass transition temperature of (A) acrylic resin can be finely adjusted, making it easier to control the adhesion and bonding conditions between materials with different polarities. As the content of (a1) methyl methacrylate increases, the glass transition temperature of (A) acrylic resin tends to increase. An example of a polar material is the electrolyte membrane of a fuel cell, and an example of a non-polar material is a component of the fuel cell other than the electrolyte. ii) (A) Since the acrylic resin can be prevented from being decomposed by moisture and acid and causing a loss in weight, it is possible to easily prevent the sealant from losing its cohesive strength and adhesive strength under high temperature and high humidity conditions. iii) (A) The softening point of the acrylic resin can be increased, which improves the handling properties when used as a sealing material.
[0017] The content of (a1) methyl methacrylate in the total amount of raw material monomers is preferably from 10 to 45% by mass, more preferably from 15 to 40% by mass, and even more preferably from 20 to 35% by mass.
[0018] (a2) Styrene Styrene is a non-polar component whose constituent element is CH, and therefore can easily improve the adhesion between materials with different polarities. Styrene also has a relatively high glass transition temperature, and can improve the cohesive force of the resin composition, which can easily improve the heat-resistant adhesion of the resin composition. Furthermore, by including styrene, it is easy to reduce the tack of the sealing material layer. On the other hand, if the content ratio of (a2) styrene is too high, the hardness of the sealing material layer increases, and it may become difficult to follow the shape of the adherend. For this reason, it is preferable to adjust the content ratio of (a2) styrene in consideration of the balance between the above-mentioned effect and the hardness of the sealing material layer.
[0019] A common method for imparting heat-resistant adhesive properties to a resin composition is to blend additives such as a silane coupling agent and a tackifier into the resin. However, blending additives may cause the additives to bleed out from the sealant layer. On the other hand, the method of using (a2) styrene as a raw monomer for (A) acrylic resin is preferable in that the bleed-out problem does not occur.
[0020] The content of (a2) styrene relative to the total amount of raw material monomers is preferably from 1 to 30% by mass, more preferably from 5 to 25% by mass, and even more preferably from 10 to 20% by mass.
[0021] (a3) Glycidyl (meth)acrylate The (A) acrylic resin must contain less than 3.0 mol% of (a3) glycidyl (meth)acrylate based on the total amount of raw material monomers. If the content of (a3) glycidyl (meth)acrylate is 3.0 mol% or more, the adhesion between the sealing material layers cannot be improved. On the other hand, if the raw material monomers of the (A) acrylic resin do not contain (a3) glycidyl (meth)acrylate, the reworkability cannot be improved.
[0022] The content of (a3) glycidyl (meth)acrylate in the total amount of raw material monomers is preferably from 0.1% by mass to less than 3.0% by mass, and more preferably from 0.5% by mass to 2.0% by mass.
[0023] As the glycidyl (meth)acrylate, either glycidyl acrylate or glycidyl methacrylate can be suitably used, but from the viewpoint of polymerization versatility, it is more preferable to use glycidyl methacrylate.
[0024] (a4) Ethyl (meth)acrylate The (A) acrylic resin preferably further contains (a4) ethyl (meth)acrylate as a raw material monomer. By containing (a4) ethyl (meth)acrylate, the glass transition temperature of the (A) acrylic resin can be easily adjusted to 35° C. or lower.
[0025] The content of (a4) ethyl (meth)acrylate relative to the total amount of raw material monomers is preferably 30% by mass or more and 95% by mass or less, more preferably 40% by mass or more and 85% by mass or less, and even more preferably 50% by mass or more and 75% by mass or less, in order to make it easy to adjust the glass transition temperature of (A) acrylic resin to 5°C or more and 35°C or less.
[0026] As the ethyl (meth)acrylate, either ethyl acrylate or ethyl methacrylate can be suitably used, but it is more preferable to use ethyl acrylate from the viewpoints of ease of copolymerization, industrial versatility, and ease of adjusting the softening point.
[0027] Other Monomers The raw material monomers of the (A) acrylic resin may further contain other monomers, such as acrylic acid, methacrylic acid, 2-hydroxymethacrylate, acrylamide, and methacrylamide.
[0028] (A) The acrylic resin is a copolymer obtained by copolymerizing raw material monomers. Examples of the copolymerization method include suspension polymerization, emulsion polymerization, solution polymerization, etc. Among these copolymerization methods, suspension polymerization is preferred because it can give a polymer with a narrow molecular weight distribution and a small amount of residual monomers, it can give a high molecular weight polymer, it does not require an emulsifier and therefore contains a small amount of impurities, and it is easy to give a copolymer resin with excellent water resistance and heat resistance. Regarding the polymerization conditions, in the case of suspension polymerization, the polymerization is preferably carried out at 50 to 80° C. for 2 to 24 hours. The copolymer may be in any form, such as alternating, random, block or graft.
[0029] In the aqueous suspension polymerization, one or more suspension stabilizers can be used, examples of which include water-soluble polymers such as polyvinyl alcohol, partially saponified polyvinyl alcohol, polyvinylpyrrolidone, (meth)acrylates, polyacrylamide, partially saponified polyacrylamide, carboxymethyl cellulose, methyl cellulose, and ethyl cellulose, and inorganic salt powders such as calcium phosphates and calcium carbonate.
[0030] It is preferable that the polymerization initiator generates polymerization initiating radical species after decomposition that are oil-soluble. Typical examples of the radical polymerization initiator include an azo-based radical polymerization initiator and a peroxide-based radical polymerization initiator. Examples of the azo radical polymerization initiator include 2,2'-azobispropane, 2,2'-dichloro-2,2'-azobispropane, 1,1'-azo(methylethyl) diacetate, 2,2'-azobis(2-amidinopropane) hydrochloride, 2,2'-azobis(2-aminopropane) nitrate, 2,2'-azobisisobutane, 2,2'-azobisisobutylamide, 2,2'-azobisisobutyronitrile, 2,2'-azobis-2-methylmethylpropionate, 2,2' -Dichloro-2,2'-azobisbutane, 2,2'-azobis-2-methylbutyronitrile, 2,2'-azobisisobutyric acid dimethyl, 1,1'-azobis(1-methylbutyronitrile-3-sodium sulfonate, 2-(4-methylphenylazo)-2-methylmalonodinitrile, 4,4'-azobis-4-cyanovaleric acid, 3,5-dihydroxymethylphenylazo-2-allylmalonodinitrile, 2,2'-azobis-2-methylvaleronitrile, 4,4'-azobis Dimethyl azobis-4-cyanovalerate, 2,2'-azobis-2,4-dimethylvaleronitrile, 1,1'-azobiscyclohexanenitrile, 2,2'-azobis-2-propylbutyronitrile, 1,1'-azobiscyclohexanenitrile, 2,2'-azobis-2-propylbutyronitrile, 1,1'-azobis-1-chlorophenylethane, 1,1'-azobis-1-cyclohexanecarbonitrile, 1,1'-azobis-1-cycloheptanenitrile, 1 ,1'-azobis-1-phenylethane, 1,1'-azobiscumene, 4-nitrophenylazobenzyl cyanoethyl acetate, phenylazodiphenylmethane, phenylazotriphenylmethane, 4-nitrophenylazotriphenylmethane, 1,1'-azobis-1,2-diphenylethane, poly(bisphenol A-4,4'-azobis-4-cyanopentanoate), poly(tetraethylene glycol-2,2'-azobisisobutyrate), and the like. Examples of the peroxide radical polymerization initiator include acetyl peroxide, cumyl peroxide, tert-butyl peroxide, propionyl peroxide, benzoyl peroxide, 2-chlorobenzoyl peroxide, 3-chlorobenzoyl peroxide, 4-chlorobenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, 4-bromomethylbenzoyl peroxide, lauroyl peroxide, potassium persulfate, diisopropyl peroxycarbonate, tetralin hydroperoxide, 1-phenyl-2-methylpropyl-1-hydroperoxide, tert-butyl pertriphenylacetate, tert-butyl hydroperoxide, tert-butyl performate, tert-butyl peracetate, tert-butyl benzoate, tert-butyl perphenylacetate, tert-butyl per-4-methoxyacetate, and tert-butyl per-N-(3-toluyl)carbamate. Examples of the polymerization initiator include peroxides such as benzoyl peroxide, lauroyl peroxide, cumene hydroperoxide, t-butyl hydroperoxide, di-t-butyl peroxide, and methyl ethyl ketone peroxide.
[0031] In addition, a mercapto compound can be added as a chain transfer agent. For example, mercaptoethanol, mercaptopropanol, mercaptobutanol, mercaptopropanediol, mercaptobutanediol, hydroxybenzenethiol and its derivatives are chain transfer agents having a hydroxyl group; 1-butanethiol, butyl-3-mercaptopropionate, methyl-3-mercaptopropionate, 2,2-(ethylenedioxy)diethanethiol, ethanethiol, 4-methylbenzenethiol, dodecyl mercaptan, propanethiol, butanethiol, pentanethiol, 1-octanethiol, cyclopentanethiol, cyclohexanethiol, thioglycerol, 4,4-thiobisbenzenethiol, etc. can be mentioned.
[0032] The weight average molecular weight of the (A) acrylic resin is preferably from 100,000 to 1,000,000, more preferably from 150,000 to 800,000, and even more preferably from 200,000 to 600,000. By setting the weight-average molecular weight to 100,000 or more, it is possible to easily improve the adhesive strength in a high-temperature environment, and by setting the weight-average molecular weight to 1,000,000 or less, it is possible to easily suppress gelation during polymerization.
[0033] The (A) acrylic resin preferably has an epoxy equivalent of 2000 g / eq or more and 30000 g / eq or less, and more preferably 4000 g / eq or more and 20000 g / eq or less. By making the (A) acrylic resin have an epoxy equivalent of 2000 g / eq or more, it is possible to easily improve the adhesion between the sealing material layers. By making the (A) acrylic resin have an epoxy equivalent of 30000 g / eq or less, it is possible to easily increase the cohesive force of the sealing material layer. By increasing the cohesive force of the sealing material layer, it is possible to easily suppress foaming of the sealing material layer when moisture contained in the electrolyte membrane is gasified and released during heat pressing.
[0034] The resin composition of the present invention is required to contain, in addition to the above-mentioned (A) acrylic resin, (B) an epoxy resin and (C) an epoxy resin curing agent. Furthermore, the resin composition of the present invention requires that the total content of the epoxy resin (B) and the epoxy resin curing agent (C) is 1 part by mass or more and 30 parts by mass or less per 100 parts by mass of the acrylic resin (A). By making the total content of the epoxy resin (B) and the epoxy resin curing agent (C) 1 part by mass or more, it is possible to easily improve reworkability. By making the total content of the epoxy resin (B) and the epoxy resin curing agent (C) 30 parts by mass or less, it is possible to easily improve adhesion between sealing material layers. The total content of the (B) epoxy resin and the (C) epoxy resin curing agent is preferably 1 part by mass or more and 25 parts by mass or less, and more preferably 1 part by mass or more and 20 parts by mass or less, per 100 parts by mass of the (A) acrylic resin.
[0035] The ratio of the active hydrogen equivalent (g / eq) of the epoxy resin curing agent (C) to the epoxy equivalent (g / eq) of the epoxy resin (B) is preferably 0.8 or more and 1.2 or less.
[0036] <(B) Epoxy resin> The (B) epoxy resin may be at least one selected from phenol novolac type epoxy resins, bisphenol A type epoxy resins, and bisphenol F type epoxy resins. Among these, phenol novolac type epoxy resins are preferred in that they have low water absorption and therefore excellent stability over time of the adhesiveness of the sealing material layer.
[0037] The epoxy equivalent of the (B) epoxy resin is preferably 150 g / eq or more and 1500 g / eq or less, and more preferably 150 g / eq or more and 1000 g / eq or less. By making the epoxy equivalent of the (B) epoxy resin 1500 g / eq or less, it becomes easier to uniformly disperse the (B) epoxy resin in the (A) acrylic resin.
[0038] The weight average molecular weight of the (B) epoxy resin is preferably from 250 to 5000, and more preferably from 300 to 3000. By setting the weight average molecular weight to 5000 or less, the (B) epoxy resin can be easily uniformly dispersed in the (A) acrylic resin.
[0039] <(C) Epoxy resin hardener> (C) Epoxy resin curing agents include polyamine-based curing agents, acid anhydride-based curing agents, thiol-based curing agents, imidazole compounds, ketimine compounds, latent curing agents such as dicyandiamide, etc. Among these, polyamine-based curing agents that can easily lower the reaction temperature are preferred.
[0040] Examples of polyamine-based curing agents include aliphatic polyamines, aromatic polyamines, polyamidoamines, etc. Among these, aliphatic polyamines are preferred because they tend to lower the reaction temperature.
[0041] The polyamine-based curing agent preferably has an active hydrogen equivalent of 50 g / eq or more and 700 g / eq or less, more preferably 75 g / eq or more and 500 g / eq or less. By making the active hydrogen equivalent of the polyamine-based curing agent 50 g / eq or more, the pot life of the resin composition can be easily extended. By making the active hydrogen equivalent of the polyamine-based curing agent 700 g / eq or less, the reaction with the (B) epoxy resin can easily proceed, and a resin composition with better durability can be obtained.
[0042] (Other additives) The resin composition may contain additives such as pigments, flame retardants, ultraviolet absorbers, antioxidants, antistatic agents, and silane coupling agents, as long as the effects of the present invention are not impaired.
[0043] [Sealing material] The sealing material of the present invention is formed from the above-mentioned resin composition of the present invention. The form of the sealing material is preferably a solid such as a particle form or a sheet form, and more preferably a sheet form from the viewpoint of handling. When forming the sealing material of the present invention into a sheet, from the viewpoint of ease of handling, it is preferable to form a sealing material layer by applying a sealing material layer forming composition obtained by dissolving the above-mentioned resin composition of the present invention in a solvent onto a substrate and drying it.
[0044] The sealing material of the present invention may be embodied in the following manner: Fig. 3 is a cross-sectional view showing the following embodiment: The sealing material of the following embodiment is preferably in the form of a sheet. <Embodiments of sealing materials> A sealing material having a first substrate, a sealing material layer, and a second substrate in this order, wherein the sealing material layer is formed from the resin composition of the present invention described above, and at least one of the first substrate and the second substrate is peelable.
[0045] Examples of the first substrate and the second substrate include plastic films such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polycarbonate, polyethylene, polypropylene, polystyrene, triacetyl cellulose, poly(meth)acrylate, polyvinyl chloride, polyphenylene sulfide, etc.; paper; etc. Among these, plastic films are preferred, and polyethylene naphthalate films are more preferred. The thickness of the first substrate and the second substrate is preferably 10 μm or more and 100 μm or less, and more preferably 25 μm or more and 75 μm or less.
[0046] At least one of the first and second substrates is preferably subjected to a surface release treatment to facilitate peeling from the sealing material layer. The release agent for the release treatment is preferably a non-silicone release agent such as polyolefin, in order to suppress adverse effects caused by migration of the release component to the electrolyte membrane and the sealing material layer.
[0047] The thickness of the sealing material layer is preferably from 10 μm to 500 μm, and more preferably from 20 μm to 200 μm.
[0048] The sealing material of the present invention can be used in the sealing portions of fuel cells, more specifically, in the sealing portions of cells that constitute the fuel cell. When in use, for example, the sealing material is heated to seal the sealing portions of the cells. The sealing material of the present invention can also be used in sealing portions of a water electrolysis device, more specifically, in sealing portions of cells that constitute the water electrolysis device.
[0049] [Polymer electrolyte fuel cell] The polymer electrolyte fuel cell of the present invention comprises a sealed portion formed by the sealing material of the present invention. FIG. 1 is a cross-sectional view showing an example of a cell constituting a typical fuel cell. The cell 10 is composed of a composite (MEA: Membrane and Electrode Assembly) consisting of a solid polymer electrolyte membrane 11 and a pair of electrodes (anode, cathode) 12, 13 arranged on both sides of the membrane, separators (14, 15) arranged on both sides of the composite and having gas flow paths (14a, 15a) for supplying a fuel gas and an oxidizer gas, respectively, and a sealing material 16 that seals between the composite and the separators (14, 15). A typical fuel cell is constructed by stacking several tens to several hundreds of cells 10, sandwiching the stack between end plates via current collector plates and insulating plates, and fastening them from both ends with fastening bolts. The cell 10 in Fig. 1 does not have an area where the sealing material layers face each other and are bonded to each other. However, in recent years, cells 10 having an area where the sealing material layers face each other and are bonded to each other as shown in Fig. 2 have also been used.
[0050] The sealing material of the present invention can be suitably used as a sealing material in the above-mentioned general-purpose fuel cell, and in particular, the sealing material of the present invention can be suitably used as a sealing material in a fuel cell having an area where sealing material layers are bonded to each other while facing each other.
[0051] [Water electrolysis device] The water electrolysis apparatus of the present invention comprises a sealed portion formed by the sealing material of the present invention. The sealed portion is preferably a sealed portion of a cell constituting the water electrolysis apparatus. EXAMPLES
[0052] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples in any way.
[0053] 1. Measurement and Evaluation The sealing materials of the examples and comparative examples were subjected to the following measurements and evaluations. The results are shown in Table 2.
[0054] 1-1.Reworkability The sealing materials of the examples and comparative examples were cut to a width of 2.5 cm and a length of 12.5 cm to prepare samples. A PET film (thickness 25 μm, width 2.5 cm, length 12.5 cm) was superimposed on the sealing material layer of the cut sample and laminated under a room temperature atmosphere to prepare evaluation sample 1. After leaving the evaluation sample 1 in a room temperature atmosphere for 1 minute, the PET film was pulled at an angle of 90°, at a speed of 100 mm / min, and at room temperature using a Tensilon type tensile tester to measure the peel strength between the sealing material layer and the PET film. The smaller the peel strength, the better the reworkability. A peel strength of 0.050 N / mm or less is considered to be good reworkability.
[0055] 1-2. Adhesion strength 1 (adhesion strength between sealing material layers) The sealing materials of the examples and comparative examples were cut to 5 cm wide and 10 cm long to prepare two samples each. The two cut samples were overlapped with the sealing materials facing each other, temporarily laminated with a heating roller at 100°C, and then permanently bonded with a heat press at 140°C, 0.2 MPa, and 30 seconds. After the permanent bonding, the samples were cut into strips 1 cm wide and 10 cm long to prepare evaluation sample 2. One cut sample of evaluation sample 2 was pulled at an angle of 180°, at a speed of 10 mm / min, and in a room temperature atmosphere using a Tensilon type tensile tester to measure the peel strength between the sealing layers. A peel strength of 0.20 N / mm or more can be said to indicate good adhesion between the sealing layers.
[0056] 1-3. Adhesion strength 2 (adhesion strength between sealing material layer and electrolyte membrane) The sealing materials of the example and comparative example were cut into samples each having a width of 5 cm and a length of 10 cm to prepare two pieces. The two cut samples and the electrolyte membrane were stacked in the following order, laminated temporarily with a heated roller at 100°C, and then heat pressed at 140°C, 0.2 MPa, and 30 seconds for full bonding. After full bonding, the samples were cut into strips with a width of 1 cm and a length of 10 cm to prepare evaluation sample 3. The electrolyte membrane used was "Nafion NRE-212 (product name), 50 μm thick" manufactured by DuPont. One cut sample of the evaluation sample 3 was pulled at an angle of 180°, at a speed of 10 mm / min, and in a room temperature atmosphere using a Tensilon tensile tester, and the peel strength between the sealant layer and the electrolyte membrane of one cut sample was measured. A peel strength of 0.20 N / mm or more indicates good adhesion between the sealant layer and the electrolyte membrane. In Comparative Example 7, the sealant layer of the sample was foamed during the preparation of the evaluation sample, so the peel strength could not be measured. <Stacking order> First substrate of the first cut sample, sealing material layer of the first cut sample, electrolyte membrane, sealing material layer of the second cut sample, first substrate of the second cut sample
[0057] 1-4. Adhesion strength 3 (Hot water durability adhesion strength between sealing material layer and electrolyte membrane) The evaluation sample 3 was immersed in a heat-resistant bottle containing ion-exchanged water, and then the heat-resistant bottle containing the sample was placed in an oven at 95°C for 500 hours. After 500 hours, the evaluation sample 3 was removed from the 95°C hot water and left in a room temperature atmosphere for 24 hours. Then, one of the cut samples was pulled at an angle of 180°, at a speed of 10mm / min, and in a room temperature atmosphere using a Tensilon type tensile tester, and the peel strength between the sealant layer and the electrolyte membrane of one of the cut samples was measured. However, the peel strength could not be measured in Comparative Examples 2 and 3, in which the electrolyte membrane peeled off after the evaluation sample was removed from the hot water. It can be said that the adhesive strength between the sealant layer and the electrolyte membrane is good when the peel strength is 0.50N / mm or more. In Comparative Example 7, the sealant layer of the sample was foamed when the evaluation sample was prepared, so the peel strength could not be measured.
[0058] 1-5. Theory Tg The theoretical Tg of the (A) acrylic resin obtained in the examples and comparative examples was calculated by the following FOX formula. The following FOX formula expresses the glass transition temperature of the homopolymer of each monomer constituting a polymer consisting of n kinds of monomers as Tg i (K), and the mass fraction of each monomer is W i Let (W1+W2+…+W i +…W n =1.) (FOX style) 1 / Tg=W1 / Tg1+W2 / Tg2+…+W i / Tg i +…+W n / Tg n
[0059] 2. Preparation of sealing material <Example 1> [(A) Preparation of acrylic resin] A homogeneous mixture containing 200 parts by mass of water containing 0.2% by mass of polyvinyl alcohol, 10 parts by mass of styrene monomer (ST), 25 parts by mass of methyl methacrylate monomer (MMA), 1 part by mass of glycidyl methacrylate monomer (GMA), 64 parts by mass of ethyl acrylate monomer (EA), 0.1 parts by mass of benzoyl peroxide as a polymerization initiator, and a chain transfer agent for molecular weight adjustment was placed into a 1-L separable flask. The mixture was heated to 70°C while stirring under a nitrogen atmosphere, and suspension polymerization was carried out for 4 hours. Next, water was removed from the suspension by decantation. The solid matter was washed with water while suction filtering, and after removing water, it was vacuum dried at 60°C to obtain acrylic resin C as the acrylic resin (A) used in Example 1. The weight average molecular weight of acrylic resin C is 31 × 10 4 The monomer composition and molecular weight are shown in Table 1.
[0060] [Preparation of resin composition] (A) An acrylic resin, (B) an epoxy resin, and (C) an epoxy resin curing agent were mixed in the ratio shown in Table 2 to obtain a resin composition of Example 1. In Table 2, the "type" of epoxy resin (B) "1" is a bisphenol A type epoxy resin (weight average molecular weight 370, manufactured by Mitsubishi Chemical Corporation, product name jER828, epoxy equivalent 185), and the "type" of epoxy resin "2" is a phenol novolac type epoxy resin (manufactured by Nippon Kayaku Co., Ltd., product name NC-3000, epoxy equivalent 270). In Table 1, the (C) epoxy resin curing agent is a polyamine-based curing agent (manufactured by Huntsman, product name JEFFAMINE D-400, active hydrogen equivalent 100).
[0061] [Preparation of sheet-shaped sealing material] The prepared resin composition and methyl ethyl ketone were mixed to prepare a coating solution for forming a sealant layer. The coating solution for forming a sealant layer was applied onto a polyethylene naphthalate film having a thickness of 25 μm, and then dried at 100° C. for 2 minutes to form a sealant layer having a thickness of 20 μm, thereby obtaining the sealant of Example 1.
[0062] <Examples 2 to 13 and Comparative Examples 1 to 8> The resin compositions and sealing materials of Examples 2 to 13 and Comparative Examples 1 to 8 were obtained in the same manner as in Example 1, except that the compounding ratio and weight average molecular weight of the raw material monomers of (A) the acrylic resin were set to the values in Table 1, and the compounding ratio of (A) the acrylic resin, (B) the epoxy resin, and (C) the epoxy resin curing agent in the resin composition was set to the values in Table 2. The weight average molecular weight of each Example and Comparative Example was adjusted by the amount of the chain transfer agent.
[0063] [Table 1]
[0064] [Table 2]
[0065] From the results in Tables 1 and 2, it can be confirmed that the resin composition for the sealing material of the embodiment can improve the reworkability and the adhesion between the sealing material layers (adhesion strength 1). Furthermore, it can be confirmed that the resin composition for the sealing material of the embodiment can improve the adhesion between the sealing material layer and the electrolyte membrane (adhesion strengths 2 and 3). [Explanation of symbols]
[0066] 10: Cell 11: Electrolyte membrane 12,13 : Electrode 14,15:Separator 14a, 15a: Gas flow path 16: Sealing material 16a: First substrate 16b: sealing material layer 16c: second substrate
Claims
1. A resin composition for a sealing material, comprising: The resin composition contains (A) an acrylic resin, (B) an epoxy resin, and (C) an epoxy resin curing agent, The (A) acrylic resin has a glass transition temperature of 5° C. or more and 35° C. or less, The (A) acrylic resin is a copolymer of raw material monomers including (a1) methyl methacrylate, (a2) styrene, and (a3) glycidyl (meth)acrylate, The proportion of the (a3) glycidyl (meth)acrylate relative to the total amount of the raw material monomers is less than 3.0 mass%, a total content of the epoxy resin (B) and the epoxy resin curing agent (C) is 1 part by mass or more and 30 parts by mass or less per 100 parts by mass of the acrylic resin (A).
2. 2. The resin composition according to claim 1, wherein the epoxy resin (B) is at least one selected from the group consisting of a phenol novolac type epoxy resin, a bisphenol A type epoxy resin, and a bisphenol F type epoxy resin.
3. The resin composition according to claim 1, wherein the epoxy equivalent of the epoxy resin (B) is 150 g / eq or more and 1500 g / eq or less.
4. The resin composition according to claim 1 , wherein the epoxy resin curing agent (C) is a polyamine-based curing agent.
5. A sealing material formed from the resin composition according to claim 1.
6. A sealing material having a first substrate, a sealing material layer, and a second substrate in this order, the sealing material layer being formed from the resin composition described in claim 1, and at least one of the first substrate and the second substrate being peelable.
7. The sealing material according to claim 5 or 6, which is a sealing material for a polymer electrolyte fuel cell.
8. The sealing material according to claim 5 or 6, which is a sealing material for a water electrolysis device.
9. A polymer electrolyte fuel cell comprising a sealed portion formed by the sealing material according to claim 7.
10. 10. The solid polymer electrolyte fuel cell according to claim 9, wherein the solid polymer electrolyte fuel cell has an area in which the sealing material layers are bonded to each other while facing each other.
11. A water electrolysis device comprising a sealed portion formed by the sealing material according to claim 8.
Citation Information
Patent Citations
Epoxy resin composition
JP1996245858A
Resin composition for solid polymer fuel cell sealing material, sealing material for solid polymer fuel cell using the resin composition, and solid polymer fuel cell using the sealing material
JP2015002029A
Method of manufacturing fuel cell separator
JP2019091535A
Resin composition for solid polymer type fuel cell seal material and seal material using resin composition, and solid polymer type fuel cell using seal material
JP2023017551A
Curable epoxy resin composition
WO2014109212A1
